Outcome of caudal superficial epigastric axial pattern flaps in dogs and cats: 70 cases (2007‐2020). (22nd December 2021) - Forster, K.; Cutando, L. S.; Ladlow, J.; Anderson, D.; Burton, C.; Das, S.; Gibson, S.; Kulendra, N.; Emmerson, T.; Baines, S.; Rutherford, L.; Paulino, R. D.; et al.
Abstract : Objectives: To describe the outcome and complications associated with the use of caudal superficial epigastric axial pattern flaps in dogs and cats. Material and Methods: Multicentre retrospective review and descriptive study of clinical records of dogs and cats having undergone caudal superficial epigastric axial pattern flaps between 2007 and 2020. Data retrieved included signalment, aetiology of surgical defect, tumour type, presence/absence of clean surgical margins, presence/absence of post‐operative wound infection, use of peri‐ and post‐operative antibiotics, duration of anaesthesia, duration of surgery, presence and duration of hypothermia, presence and duration of hypotension, presence/absence of post‐operative surgical drain and length of caudal superficial epigastric axial pattern flap. The incidence of complications and outcomes were documented. Results: Seventy cases met the inclusion criteria; 51 dogs and 19 cats. In dogs, 67% of cases developed complications (59% minor, 8% major) and 33% had uneventful wound healing. In cats, 53% of cases developed complications, (47% minor, 5% major) and 47% had uneventful wound healing. In dogs, the percentage of cases experiencing dehiscence, necrosis, seroma, oedema and post‐operative infection was 31%, 29%, 26%, 26% and 16% respectively. In cats, this was 26%, 16%, 11%, 0% and 5% respectively. A good overall outcome was seen in 77% of dogs and 79% of cats. A poor overall outcome was seen in 4% of dogs and 0% of cats. Clinical Significance: Caudal superficial epigastric axial pattern flaps are traditionally thought more robust than other flaps, yet complication rates remain high, despite a high overall success rate.